Selected Decisions (10th Ed). (Selected Decisions; Issue, Year, 1983)
This paper presents Selected Decisions and Selected Documents' Tenth Issue of the IMF. This volume, the Tenth Issue of Selected Decisions of the IMF and Selected Documents, contains the decisions, interpretations, and resolutions of the Executive Board and the Board of Governors of the IMF to which frequent reference is made in the current activities of the IMF. In addition, the volume contains certain selected documents relating to the Fund and the United Nations. This issue contains most of the decisions published in the Ninth Issue that remain in effect, as well as new decisions adopted since the publication of that issue. With few exceptions, the decisions in this volume are of a general nature and relate to obligations, policies, or procedures under the Articles of Agreement. Decisions of the IMF that are incorporated in the By-Laws and the Rules and Regulations are not reproduced in this volume. Some of the decisions in this volume that were adopted prior to the entry into force of the Second Amendment of the IMF's Articles of Agreement on April 1, 1978 contain references to provisions of the IMF's Articles or Rules and Regulations that were changed by, or because of, the Second Amendment.